OPTIMAL SIMULATION DESIGN OF SPACEBORNE CONNECTOR - YU ChengYue; LIU Bo; WANG ChunPeng; XUE Chuang; AN MingXin (Jixie qiangdu)
In the design and research on the spaceborne connector of aerospace satellites, a joint optimization method is proposed. In order to reduce the problem of excessive bolt axial force of the spaceborne connector, a method with the variance of the bolt axial force as the objective function and constraint conditions is proposed. Free size optimization mathematical model, using OptiStruct optimization module for optimization simulation, a comparative analysis of the bolt loading before and after optimization, and a detailed description of the optimization iteration process; based on the optimization model, the size of the support plate is optimized design. The results show that after optimization by the proposed mathematical model, the axial force of the bolt is significantly reduced, which meets the expected requirements; The optimization target is affected by different factors in different stages of the iterative process; The structural fundamental frequency can be increased by optimizing the design. The optimization method provides a reference for the optimization of bolt strength and the structural design of spacecraft.